Religious Declarations of Youth versus their Opinions...and Attitudes towards the Phenomenon of Sexting - Bereźnicka, Małgorzata; Rokitowska, Justyna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The aim of this paper is to present the results of a survey on the opinions of high school graduates and their attitudes towards the phenomenon of sexting with regard to respondents’ religious declarations. The authors, recalling various studies, introduce the role that religiosity plays in relation to various sexual behaviours. After that the authors present the analysis and results of their survey, taking into consideration three groups of students: practising Catholics, non-practising Catholics and atheists. The similarities as well as the discrepancies among these groups are discussed. The paper shows that students’ declarations connected with faith are not always consistent with their opinions on the discussed subject, which can be seen especially in the group of non-practising Catholics. At the end, key conclusions and postulates for the practice are presented.